Mapping the Future of Renewable Energy: Identifying Solar and Wind Power Zones for Sustainable-Based Super Smart Grid Development in China - Sadaf Ashraf ,; Engr. Kashif Abbas,; Muhammad Abdullah,; Rameez Akbar Talani,; Muhammad Anwar Ul Haq,; Abdul Qadeer,; Syed Wazeer Ul Hassan Naqvi,; Syed Jaffar Hussain Shah, (Dialogue Social Science Review (DSSR), 2025)
Approximately 17.2% of global population lives in China. The power generation of these population relies heavily on Non-renewable energy sources, resulting in large greenhouse gases emission into the atmosphere. In order to protect the environment, the China has decided to construct an extremely intelligent smart grid based on sustainable energy sources but the ability to develop such a super power grid is unclear because of the absence of Effective strategic assessment and an insufficient information about the potential sites of RERs. This paper explores the potential of solar and wind energy in China, with a focus on identifying key regions for renewable energy development to support the country’s transition to a sustainable-based super smart grid. As China accelerates its renewable energy goals, the effective integration of solar and wind power is essential for ensuring grid stability, enhancing energy efficiency, and reducing carbon emissions. Through a comprehensive geospatial analysis, this paper identifies high-potential zones for solar and wind energy in regions such as Xinjiang, Gansu, Qinghai, Inner Mongolia, and coastal provinces. Additionally, the role of a super smart grid characterized by advanced grid technologies, automation, and energy storage solutions is discussed in the context of China’s energy infrastructure transformation. The paper also examines the technological and policy challenges associated with integrating renewable energy into a smart grid system, including the need for enhanced energy storage, grid modernization, and optimized energy management. Drawing on case studies of successful projects and pilot initiatives, this paper highlights the opportunities and challenges of building a sustainable, renewable-based super smart grid in China. The findings emphasize the critical importance of targeted policy frameworks, technological innovation, and large-scale investments to realize the full potential of renewable energy resources and support China’s clean energy future.